2009
DOI: 10.1148/radiol.2513080884
|View full text |Cite
|
Sign up to set email alerts
|

Simple Developmental Dyslexia in Children: Alterations in Diffusion-Tensor Metrics of White Matter Tracts at 3 T

Abstract: Findings at 3.0-T DT imaging suggest that white matter differences in dyslexic children are not limited to the portion of the brain traditionally considered to be integral to word recognition and processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 36 publications
3
35
1
1
Order By: Relevance
“…Even if not yet validated on a large number of specimens, this bundle may represent the key of the visual limbic pathway that subserves emotional, learning, and memory functions that are modalityspecific to vision [18]. Several DTI studies reported correlations between reduced FA in some portions of the ILF and impairments of higher visuo-perceptual functions [76] including object and picture naming [57,81], dyslexia [28,74,84], and alexia [32]. Moreover, according to Catani et al [14] the role of this ventral bundle is even more complex.…”
Section: Li-am Bundlementioning
confidence: 99%
“…Even if not yet validated on a large number of specimens, this bundle may represent the key of the visual limbic pathway that subserves emotional, learning, and memory functions that are modalityspecific to vision [18]. Several DTI studies reported correlations between reduced FA in some portions of the ILF and impairments of higher visuo-perceptual functions [76] including object and picture naming [57,81], dyslexia [28,74,84], and alexia [32]. Moreover, according to Catani et al [14] the role of this ventral bundle is even more complex.…”
Section: Li-am Bundlementioning
confidence: 99%
“…We included a large sample of children with varying performance levels, including children with learning deficits in reading and/or maths. White matter connections in broad clusters were associated with learning scores for both reading and maths that extended well beyond focal differences in fronto-temporal and fronto-parietal regions that had been previously implicated (Carter et al 2009, Rollins et al 2009, Odegard et al 2009, Matejko et al 2013, Kucian et al 2013, Beek et al 2014. Furthermore, better reading and maths scores were related to two key measures of global brain network organisation: shorter path length and higher clustering.…”
Section: Discussionmentioning
confidence: 68%
“…These are largely derived a priori from adult neuropsychological models or from the use of statistical procedures optimised to uncover maximal focal differences in canonical case-control designs (Carter et al 2009, Rollins et al 2009, Odegard et al 2009, Matejko et al 2013, Kucian et al 2013, Beek et al 2014. While these approaches have been invaluable for discovering the brain basis of acquired adult disorders, their applicability to disorders of developmental origin has been questioned for some time (Karmiloff-Smith 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect subtle changes, quantitative analysis of DTI metrics such as fractional anisotropy and axial and radial diffusivities are measured. [1][2][3] However, these DTI metrics are subject to high uncertainties and bias caused by noise in the images. [4][5][6][7] Seo et al have reported SNR requirements for various anatomical areas of the brain and FA values for bias-free estimation of tensor metrics.…”
Section: Introductionmentioning
confidence: 99%